2008
DOI: 10.1021/op800063n
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Focused Beam Reflectance Measurement (FBRM) Data via Simulated Crystallization

Abstract: Focused beam reflectance measurement (FBRM) has gained much popularity as a tool for particle system characterization both in crystallization research and in manufacturing. The precise interpretation of FBRM data, however, still remains an issue of some conjecture and dispute. This study examines the relationship among total counts of chord lengths, statistics of chord length distribution, particle number and average particle size in simulated crystallization, which involves selective introduction of predeterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 28 publications
2
46
0
1
Order By: Relevance
“…In previous works [7][8][9][21][22][23]] the values of L min and L max were estimated from suitable measurements. However, the technique of estimating L min and L max directly from the bin boundaries of the CLD histogram using a moving window technique has been demonstrated to yield more accurate results [6].…”
Section: Modelling Chord Length Distributionmentioning
confidence: 99%
“…In previous works [7][8][9][21][22][23]] the values of L min and L max were estimated from suitable measurements. However, the technique of estimating L min and L max directly from the bin boundaries of the CLD histogram using a moving window technique has been demonstrated to yield more accurate results [6].…”
Section: Modelling Chord Length Distributionmentioning
confidence: 99%
“…The crystal nucleation was determined by the observation on particle counts and mean particle sizes using the FBRM. The information of total particle counts can be directly related to nucleation (Yu et al, 2008). Crystal counts were categorised into five classes: 1-5 µm (extra small crystal, XSc), 10-23 µm (small crystal, Sc), 29-86 µm (medium crystal, Mc), 100-251 µm (large crystal, Lc) and 293-1000 µm (extra large crystal, XLc).…”
Section: Crystal Size Distribution By Fbrmmentioning
confidence: 99%
“…One should therefore convert the measured CLD to its corresponding DSD. Methods were discussed to transform the measured chord length distribution into a size (diameter) distribution [ 91 94 ]. Another study had shown that the FBRM tended to undersize the droplets in emulsion [ 95 ].…”
Section: Application Of Fiber-optical Probes In Multiphase Reactorsmentioning
confidence: 99%